Disclination regulated depression and elevation of glassy nematic coatings on soft elastic substrates. (October 2020) - Qian, W.X.; Ni, Y.; He, L.H.
Abstract: We study photo-activated nonlinear deformation of periodic polydomain glassy nematic coatings on soft elastic substrates. The director fields are piecewise constant with rank-1 connection at the domain boundaries and form regular arrays of disclinations of different charges at the junctions. Based on numerical simulations, we show that conical depression and elevation appear at the positive and negative disclinations respectively. The phenomenon is attributed to bend of the coating controlled by interfacial shear force, and the mechanism can be utilized to create various novel surface topographies which have not been reported previously. Although our exploration is concerned with the theoretical aspect, the results may inspire future experimentation and provide insights for designing photo-switchable surfaces.